Minimally Invasive Resin-Bonded Inlay-Retained Cantilever Fixed Dental Prosthesis: A Clinical Report - Albandari Bin-Rubayan; Abdulaziz Samran; Ali Alqerban (Hindawi Limited, 2021)
This clinical report demonstrates the treatment of a healthy adult patient referred for prosthodontic treatment after orthodontic treatment with a resin-bonded inlay-retained cantilever fixed dental prosthesis (IRCFDP). The purpose of this report was to demonstrate the esthetic, functional, and conservative properties of a resin-bonded IRCFDP fabricated from monolithic zirconia which can be placed in posterior area in certain situations. Acceptable esthetics with a conservative and functional result were achieved by using a resin-bonded inlay-retained cantilever fixed dental prosthesis (IRCFDP). All laboratory and clinical procedures of this case report are described.